PROFIL UMUR DAN JENIS KELAMIN DIARE AKUT ROTAVIRUS DAN NON ROTAVIRUS PADA BALITA YANG DIRAWAT DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Arianto, Rezi; Putra, Dedi Satriya; D, Fauzia Adrini (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTAcute diarrhea is still the major cause of deaths in children under five years old. Based on world health organization south east Asian region (WHO SEAR) datas acute diarrhea caused 10-11% death in children under five years old. Rotavirus is the major cause of deaths in under five years old. This study aimed to know the acute rotavirus and non rotavirus diarrhea profile at arifin achmad general hospital of riau province. This is study was conducted using descriptive crosssectional methods during October 2014 until January 2015 at inpatient care of arifin achmad general hospital of riau province. From this periods, as much as 30 stool samples that gained from 43 hospitalized children’s population because of acute diarrhea. Stool smaples was observed in microbiology laboratory of faculty medicine of riau university using immunochromatograpy assay. Results, 10 stools sample were rotavirus positive (33,3%) and 20 stool samples were rotavirus negative (66,7%). Acute diarrhea thas caused by rotavirus happens at the age 6-35 months at 8 persons.Keyword: diarrhea, rotavirus,immunochromatography